Telekesehatan dan Telemedisin: Perspektif Hukum Kesehatan - Ismi Fadjriah Hamzah (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
Telehealth and telemedicine have become important innovations in health services, especially during and after the COVID-19 pandemic. This article examines the development and regulation of telehealth and telemedicine in Indonesia from a health law perspective. Using normative legal research methods, this study analyzes Law Number 17 of 2023 concerning Health and Minister of Health Regulation Number 20 of 2019 as the main legal basis. The research results show that even though there are basic regulations, there is still an urgent need to establish more comprehensive government regulations regarding telemedicine. The absence of implementing regulations has the potential to create legal uncertainty in practice. Although telehealth and telemedicine offer innovative solutions to improve access to healthcare, especially in remote areas, the development of more comprehensive regulations is urgently needed to ensure effective and ethical implementation.